2019
DOI: 10.1021/acs.iecr.9b02422
|View full text |Cite
|
Sign up to set email alerts
|

110th Anniversary: New Volumetric Frequency Response System for Determining Mass Transfer Mechanisms in Microporous Adsorbents

Abstract: A new volumetric frequency response (VFR) system was developed for studying the mass transfer characteristics of gases in microporous adsorbents. For this VFR system, the differential pressure response from a small perturbation in volume was measured in a closed system after equilibrium was established for a gas adsorbate–adsorbent pair at constant temperature and pressure. It operates over a wide range of frequencies from 10–5 to 10 Hz, from atmospheric pressure down to vacuum pressures of 100 Torr, and at te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…It also shows that gas compression effect is more severe for monatomic gases with a higher specific heat ratio k (k = 1.67) than that for linear paraffin (k = 1.04 ~ 1.32) under similar experimental conditions [54]. Hossain et al [55] confirmed this unexpected feature at higher frequencies…”
Section: Apparatus and Principle For Batch Vsfrmentioning
confidence: 80%
See 3 more Smart Citations
“…It also shows that gas compression effect is more severe for monatomic gases with a higher specific heat ratio k (k = 1.67) than that for linear paraffin (k = 1.04 ~ 1.32) under similar experimental conditions [54]. Hossain et al [55] confirmed this unexpected feature at higher frequencies…”
Section: Apparatus and Principle For Batch Vsfrmentioning
confidence: 80%
“…The heat released from compression could cause substantial spurious effects for response curves at high frequencies, resulting in interference with mass transfer dynamics. The relative importance of gas compression is found to depend mainly on the gas type, pressure, and heatexchange rate at the adsorber wall from experimental and simulation studies [53][54][55]. Figure 2a shows the simulation results of pressure in a control experiment as a sequence for gas compression-the pressure amplitude exceeds the magnitude vP 0 at higher frequencies for a control experiment, leading to negative values of the in-phase component rather than to zero when the effect of gas compression heating is neglected.…”
Section: Apparatus and Principle For Batch Vsfrmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in volume perturbation FR found that the heat released from compression could cause substantial spurious effects for response curves at high frequencies, interfering with the evaluation of mass-transfer dynamics. In order to eliminate any effects unrelated to the adsorption kinetics, a blank experiment with quartz particles was performed first at the same operating conditions. A mathematical treatment was then employed to replace the response curves (amplitude ratio and phase lag) of volume and pressure to relative pressure responses in the absence and presence of adsorbent with the same volume perturbation.…”
Section: Theorymentioning
confidence: 99%